Hubungan Tinggi Lompatan terhadap Ketepatan Smash Pemain Bola Voli Usia 16 Tahun - Puput Widodo; Dhamar Dwi Kurniawan (Journal on Education, 2024)
The low performance of the Grenggeng Volley Ball Academy (GVBA) team is a problem in this research. The results of observations made were that the level of smash accuracy of the players was low, it was hypothesized in the research that there was an influence of jump height on the level of smash accuracy of the Grenggeng men's volleyball players. The research aims to determine the relationship between jump height and smash accuracy in the volleyball game of male players at Grenggeng Volley Ball Academy (GVBA) in 2024. This research is correlational research with a survey method and data collection techniques using tests and measurements. The research subjects used were male players who took part in extracurricular volleyball games, totaling 20 children. The instruments used in this research were the vertical jump test and smash accuracy test. The data analysis technique used is simple and multiple correlation with a significance level of α = 0.05. Based on the research results from data analysis, it was possible to obtain a significant relationship between jump height and smash accuracy in the volleyball game of 16 year old Grenggeng Volley Ball Academy (GVBA) male players, with a correlation coefficient of 0.486. There is a significant relationship between jump height and smash accuracy in the volleyball game of 16 year old Grenggeng Volley Ball Academy (GVBA) male players.